Pembelajaran Jarak Jauh Selama Pandemi di Pondok Pesantren Darunajah 2 Bogor - Nur Hayati (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
In an effort to suppress the spread of the Covid-19 virus, Kemdikbud took a policy to close schools during the Covid-19 pandemic. All schools that initially did conventional learning by face-to-face, now learning is done from home through distance learning or online system, no exception pondok pesantren. The purpose of this research is to find out the distance learning process conducted by Pondok Pesantren Darunnajah 2 Cipining, Bogor. This research was conducted using descriptive qualitative approach. Based on research can be known that in learning, pesantren use various platforms such as google classroom, google meet, whatsapp, and smart system. In this online learning, the materials and tasks given are quite diverse, although there are no tasks in the form of discussions so that the interaction between students and students and teachers cannot be done. All parties, both students, teachers, and parents experienced a culture shock with the existence of this distance learning system / online. Distance learning /online also gives rise to physical distancing. Religious activities that are usually carried out in pesantren are now carried out at home and all must be reported to the teacher or room guardian via whatsapp. The challenges faced in online learning include a lack of interaction between teachers and students, a network that arises to sink, quotas that are rapidly depleted and expensive, and a lack of active participation of students. Therefore, the readiness of both teachers and students, as well as motivation from parents can also support the implementation of this distance learning process. In addition, the provision of quotas is also important to support the online learning process carried out by pesantren.